PENGARUH AKUNTANSI BERBASIS AKRUAL, SISTEM PENGENDALIAN INTERN DAN MOTIVASI KERJA PADA KUALITAS LAPORAN KEUANGAN - Setiawan, I Wayan Nico; ., Gayatri (E-Jurnal Akuntansi, 2017)
ABSTRACT Satuan Kerja Perangkat Daerah receives Unqualified Opinion opinion in 2014 and 2015, but the Audit Agency audit finds that there are still weaknesses in the internal control system, which is still a lot of supervision that needs to be improved. The research method used is purposive sampling method with criterion 47 SKPD and criteria of respondents are 141 respondents consisting of head SKPD, head of sub finance department, and head sub part of reporting participating in making financial report. Data collection was done by distributing questionnaires directly to each SKPD in Gianyar regency. The analysis technique used is multiple linear regression. The result of analysis shows that accrual based accounting in making financial report without supervision and motivation from superiors of financial statements prepared to get better result, with the internal control system that supervise and direct from principal and agent so that can give actual information to be submitted in the preparation of financial statements, the need for work motivation in making financial statements so that local governments can complete the financial statements on time and can convey the actual information for its users. This study concludes that accrual-based accounting, internal control system, and work motivation have a positive effect on the quality of financial statements   Keywords :    accrual based accounting, internal control system, work motivation, quality of financial statements